Andean rooots and tubers : Ahipa, arracacha, maca and yacon - Hermann, M.; Heller, J.
Andean roots and tubers at the crossroads -- Ahipa. Pachyrhyzus ahipa (wedd) Parodi -- Arracacha. Arracacia xanthorrhiza Bancroft -- Maca. Lepidium meyenii Walp. -- Yacon. Smallanthus sonchifolius...